A techers' curriculum guide based on the Calla Approach desing for IDSAPEDAC - Paredes Paredes, Moraima Olivia (2004)
1. Leraning vs. Teaching 2.Theoretical framework for the curriculum proposed 3. Introduction 4. Applying the curriculum in IDSAPEDAC 5. Conclusions and recommendations